Area Health: From International Experience to Model Development in Thailand - Leesmidt, Vinai; Pannarunothai, Supasit (Journal of Health Science of Thailand, 2017)
Area health is so new that Thailand has little experience about it. These critical lessons should be learned from international experiences to understand about several important issues including concept of area health, organizational structure, roles and responsibility, power relations among relevant organizations, control and monitoring mechanism and impacts of implementation of the area health. The study was a documentary research about experiences of 8 countries and the NHSOBMA branch during July 2010 - December 2010. The collected data was analyzed by content analysis and presented descriptively. The study result pointed out that there were several different words to name area health. The area health was composed of 3 concepts including integrated health service system, health care decentralization and system governance. The core organization of area health was area health board that had autonomy. The central agency remained control power. The board had network relationship with social society. Area health had 3 important functions including health care service provision, health care financing and system governance. The governance mechanisms of area health were conducted through contract and malpractice liability. Area health consisted of both advantages and disadvantages which affected health care quality, efficiency and equity. Thailand needed to improve several factors to succeed in area health implementation including policy conflict, coverage of health care network, local politics and readiness of local expertise.